2017
DOI: 10.1038/cdd.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

The LATS1 and LATS2 tumor suppressors: beyond the Hippo pathway

Abstract: Proper cellular functionality and homeostasis are maintained by the convergent integration of various signaling cascades, which enable cells to respond to internal and external changes. The Dbf2-related kinases LATS1 and LATS2 (LATS) have emerged as central regulators of cell fate, by modulating the functions of numerous oncogenic or tumor suppressive effectors, including the canonical Hippo effectors YAP/TAZ, the Aurora mitotic kinase family, estrogen signaling and the tumor suppressive transcription factor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
191
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(195 citation statements)
references
References 214 publications
(266 reference statements)
3
191
0
1
Order By: Relevance
“…Elevated YAP expression has been observed in many types of human cancers, including cancer of lung, liver, ovary, cervix, colon, and others [1,6,9,[16][17][18][19][20][21][22]. Consistently, the upstream tumor suppressors of the Hippo pathway, such as NF2 and LATS1/2, are frequently deleted or mutated in many malignancies [23,24]. Although mutations of YAP/TAZ are rare, a recent study reported that a germline point mutation of YAP (R331W) is correlated with a significantly higher incidence of lung carcinomas [25].…”
Section: Introductionmentioning
confidence: 95%
“…Elevated YAP expression has been observed in many types of human cancers, including cancer of lung, liver, ovary, cervix, colon, and others [1,6,9,[16][17][18][19][20][21][22]. Consistently, the upstream tumor suppressors of the Hippo pathway, such as NF2 and LATS1/2, are frequently deleted or mutated in many malignancies [23,24]. Although mutations of YAP/TAZ are rare, a recent study reported that a germline point mutation of YAP (R331W) is correlated with a significantly higher incidence of lung carcinomas [25].…”
Section: Introductionmentioning
confidence: 95%
“…NDR kinases such as Trc (Drosophila), NDR1 and NDR2 (NDR1/2; mammals), and SAX-1/SAX-2 (C. elegans) share evolutionarily conserved functions in coordinating neurite branching and patterning of neuronal fields 10 . Other NDR kinases such as Wts (Drosophila), LATS1 and LATS2 (LATS1/2; mammals) and WTS-1 (C. elegans) regulate polarized differentiation of epithelia and other cell types 11 . In budding yeast S. cerevisiae and fission yeast S. pombe, NDR kinases Cbk1 and Orb6 (respectively) are required for polarized cellular morphogenesis [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the Hippo pathway Lats1 and Lats2 are considered redundant, but each paralog also has unique functions such as estrogen-mediated signaling and p53 regulation, respectively. Furthermore, Lats kinases and Yap have ancient and conserved non-Hippo functions in spindle-assembly checkpoints and cytokinesis 51 . TRULI also offers the ability to investigate these non-Hippo functions of Lats kinases, and it would be prudent to understand the implications of Lats inhibition on these pathways prior to therapeutic endeavors.…”
Section: Discussionmentioning
confidence: 99%